2009
DOI: 10.1111/j.1365-2672.2008.04016.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lactic acid bacteria in Moroccan raw milk and traditionally fermented skimmed milk ‘lben’

Abstract: Aims:  To identify lactic acid bacteria (LAB) present in Moroccan dairy products to establish and preserve their microbial species diversity. Methods and Results:  Thirty‐seven samples were collected from different farms. A total of 146 LAB were isolated and subjected to (GTG)5‐PCR analysis. Comparison of the profiles with data available at the Moroccan Coordinated Collections of Micro‐organisms allowed identification of 85 isolates. The remaining 61 were subjected to SDS‐PAGE analysis of whole cell proteins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 33 publications
(67 reference statements)
7
18
0
Order By: Relevance
“…(38 %). Ouadghiri et al [28] observed similar results in a study of raw cow milk in Morocco. They discovered that L. lactis was the most common species found among all LAB, followed by Lactobacillus plantarum and Leuconostoc mesenteroides.…”
Section: Discussionsupporting
confidence: 53%
“…(38 %). Ouadghiri et al [28] observed similar results in a study of raw cow milk in Morocco. They discovered that L. lactis was the most common species found among all LAB, followed by Lactobacillus plantarum and Leuconostoc mesenteroides.…”
Section: Discussionsupporting
confidence: 53%
“…Generally, lipolysis refers to the hydrolysis of triglycerides by the enzyme lipase and results in the formation of free fatt y acids, which may be precursors of aromatic components such as methyl ketones, secondary alcohols, esters and lactones (54,55). Compared to other bacterial groups, lactic acid bacteria are considered as weakly lipolytic (56).…”
Section: Technological Suitability Of Strains As Starter Culturesmentioning
confidence: 99%
“…(2) During the process of LAB isolation, LAB colonies were randomly picked using two kinds of separation media (MRS and M17 agar plates) with 30 300 colonies. It is reported that MRS and M17 medium were the most suitable media for the isolation and counting of LAB from dairy products (Ouadghiri et al, 2009). In this study, these two media were able to isolate the most LAB species found in the fermented dairy products.…”
Section: Discussionmentioning
confidence: 48%